Unsymmetrical Binding Modes of the HOPNO Inhibitor of Tyrosinase: From Model Complexes to the Enzyme. Issue 11 (29th January 2013) - Bochot, Constance; Favre, Elisabeth; Dubois, Carole; Baptiste, Benoit; Bubacco, Luigi; Carrupt, Pierre‐Alain; Gellon, Gisèle; Hardré, Renaud; Luneau, Dominique; Moreau, Yohann; Nurisso, Alessandra; Réglier, Marius; et al.
Abstract The deciphering of the binding mode of tyrosinase (Ty) inhibitors is essential to understand how to regulate the tyrosinase activity. In this paper, by combining experimental and theoretical methods, we studied an unsymmetrical tyrosinase functional model and its interaction with 2‐hydroxypyridine‐N‐oxide (HOPNO), a new and efficient competitive inhibitor for bacterial Ty. The tyrosinase model was a dinuclear copper complex bridged by a chelated ring with two different complexing arms (namely (bis(2‐ethylpyridyl)amino)methyl and (bis(2‐methylpyridyl)amino)methyl). The geometrical asymmetry of the complex induces an unsymmetrical binding of HOPNO. Comparisons have been made with the binding modes obtained on similar symmetrical complexes. Finally, by using quantum mechanics/molecular mechanics (QM/MM) calculations, we studied the binding mode in tyrosinase from a bacterial source. A new unsymmetrical binding mode was obtained, which was linked to the second coordination sphere of the enzyme.